ANALYSIS OF FACTORS INFLUENCING MINIMUM PRICE DETERMINATION FOR NILE FISH FARMERS IN KEDURANG DISTRICT - Sella Agustin; Rika Dwi Yulihartika; Yossie Yumiati (Fakultas Pertanian, 2025)
This study aims to analyze what factors influence the minimum price setting for tilapia farmers in Kedurang sub-district. The data analysis method used is multiple linear regression analysis using SPSS. Based on the results of the study, the f test showed a Sig. value of 0.000 (<0.05), it can be concluded that the Independent Variable has a significant effect simultaneously on the Dependent Variable. The results of the t test in the form of a sig value. variable X1 Production Cost of 0.000 (<0.05), it is concluded that variable X1 Production Cost has a significant effect on variable Y minimum price setting; Sig value. variable X2 Market Demand of 0.86 (>0.05), it is concluded that the variable has no significant effect on variable Y minimum price setting; Sig value. variable X3 Government Policy of 0.377 (>0.05), it is concluded that the variable has no significant effect on variable Y; Sig value. variable X4 Product Quality of 1000 (>0.05), it is concluded that the variable has no significant effect on variable Y minimum price setting